The liberal state in international society: Interpreting recent British foreign policy. (March 2014) - Ralph, Jason
The question of who decides when a state has not met its international responsibilities (and therefore forfeits the right to non-intervention) and what kind of international action should be taken (from limited intervention to full-blown regime change) divides liberal foreign policy thinking. To understand the nature of that division, and what is at stake, this article distinguishes 'neoliberal' from 'liberal internationalist' approaches and locates them in an English School understanding of international society. Where the latter stresses the importance of observing the procedural norms centred on the United Nations, the former contests the legitimacy of such norms if they fail to deliver substantive liberal outcomes. The article then interprets British foreign policy discourse either side of the 2003 Iraq conflict through the prism of this debate. The central claim is that a more cautious approach to the use of force and American unilateralism has not silenced the critique of the UN system and that the international reaction to the Libyan intervention prompts the kind of reflection that continues to separate neoliberal from liberal internationalist approaches.